High Thyroid-Stimulating Hormone Level is Associated with the Risk of Developing Atherosclerosis in Subclinical Hypothyroidism - Gao, CX.; Yang, B.; Guo, Q.; Wei, L H; Tian, LM. (Hormone and Metabolic Research, 2015)
The aim of our study was to assess the potential role of thyroid-stimulating hormone (TSH) in the risk of developing atherosclerosis in subclinical hypothyroidism (SCH). A cohort of 240 SCH patients and 150 euthyroid volunteers were recruited for the study. SCH patients were stratified into 2 groups according to TSH levels (group A: TSH<10 mIU/l; group B: TSH>10 mIU/l). All subjects were examined for clinical and biochemical parameters. Visfatin, omentin-1, and circulating endothelial biomarkers were measured. Patients in group B received l-thyroxine replacement to achieve euthyroidism; after 6 months of euthyroidism all measurements were repeated. Patients with SCH had higher total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and C-reactive protein (CRP) levels and lower nitric oxide (NO) and omentin-1 levels compared to euthyroid subjects (all p<0.05). TC, LDL-C, and CRP decreased significantly, while NO and omentin-1 levels increased significantly after l-thyroxine replacement. Based on multivariate liner stepwise regression analysis, omentin-1 was independently correlated with BMI and TSH; NO was independently correlated with age, TSH, LDL-C, and omentin-1. High TSH level contributes to endothelial dysfunction in SCH, while TSH-induced decrease of omentin-1 provides a new link between SCH and atherogenic risk.
Keywords: thyroid-stimulating hormone; adipokines; subclinical hypothyroidism